1997
DOI: 10.1074/jbc.272.1.601
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Cyclooxygenase-2 via the NF-κB p65 Transcription Factor in Human Vascular Endothelial Cells

Abstract: The inducible cyclooxygenase, COX-2, has been associated with vascular inflammation and cellular proliferation. We have discovered that hypoxia increases expression of the COX-2 gene in human vascular endothelial cells in culture independent of other stimuli. Western analysis of human umbilical vein endothelial cells (HUVEC) revealed a greater than 4-fold induction of protein by hypoxia (1% O2). The steady-state level of COX-2 mRNA was correspondingly elevated by both Northern blot and reverse transcriptase-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
437
2
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 641 publications
(470 citation statements)
references
References 41 publications
(36 reference statements)
25
437
2
6
Order By: Relevance
“…In addition, besides HIF responsive elements, NF-B consensus sequences are also present in the miR-155 promoter indicating the capacity of NF-B-mediated stimuli to influence the HIF pathway via miR-155 [49]. Indeed, although the detailed mechanism is still not fully understood, it is clear that basal NF-B is moderately activated in hypoxia [87][88][89].…”
Section: Crosstalk With Nf-kappabmentioning
confidence: 99%
“…In addition, besides HIF responsive elements, NF-B consensus sequences are also present in the miR-155 promoter indicating the capacity of NF-B-mediated stimuli to influence the HIF pathway via miR-155 [49]. Indeed, although the detailed mechanism is still not fully understood, it is clear that basal NF-B is moderately activated in hypoxia [87][88][89].…”
Section: Crosstalk With Nf-kappabmentioning
confidence: 99%
“…It has been shown that the increase in COX-2 expression seen under hypoxic conditions is under the transcriptional control of NF-jB. 35 In addition, hypoxia inducible transcription factor 1 (HIF-1) alpha subunit activates NF-jB, and that NF-jB controls HIF-1alpha transcription, 36 which in turn, drives the de novo synthesis of Glut-1 in chronic hypoxia. 37 Current limitations to this study include the retrospective design, and the finding that use of IHC to evaluate protein levels is only semiquantitative and does not represent the structure or functionality of the protein.…”
Section: Recently Kurman Et Al Proposed a New Classification Ofmentioning
confidence: 99%
“…This creates a situation whereby both the hypoxic signalling pathway, through the Hypoxia Inducible factor (HIF), and the inflammatory signalling pathway, through Nuclear factor-!B (NF!B), are activated. Recent studies have shown that hypoxia influences the NF!B pathway and that HIF may play an important role in inflammation [4][5][6][7][8]. However, the relative contributions of HIF and NF!B into creating transcriptional activation profiles leading to a coordinated regulation of hypoxia-induced inflammatory gene expression remain unclear.…”
Section: Introductionmentioning
confidence: 99%